Provable secure ownership transfer protocol for RFID tag - Bian-qing YUAN; Ji-qiang LIU (Tongxin xuebao)
With the ownership transfer of an object,the ownership of the RFID tag attached to it also needs to be transferred.Security and privacy are the key issues while researchers studying the process of RFID tag ownership transfer.In the UC(universally composable)framework,an ideal functionality of RFID tag ownership transfer is formally defined.Then,a novel lightweight ownership transfer protocol for RFID tag is proposed.Subsequently,it is proved that proposed protocol realizes the previously defined ideal functionality and satisfies the required security properties such as mutual authentication,tag anonymity,resistance to de-synchronization attacks,forward privacy protection and backward privacy protection.Compared with the existing ownership transfer protocols for RFID tags,the computational complexity and the storage requirements of proposed protocol are all lower.Meanwhile,the number of interaction among the entities is small.Therefore,the proposed protocol can efficiently implement ownership transfer for low-cost tags.